LOCAL ECOLOGICAL RITUALS AND ENVIRONMENTAL EDUCATION: CULTIVATING ECOLOGICAL ETHOS AND ENVIRONMENTAL RIGHTS IN INDONESIA - Aji Baskoro (Al-Qalam, 2026)
The increasing complexity of the global environmental crisis necessitates more contextual, culturally grounded, and transformative approaches to environmental education. Conventional models of environmental education often rely on technocratic and universalized frameworks that insufficiently engage with local cultural values and indigenous ecological knowledge systems. This study examines the potential of local ecological rituals in Indonesia, including Nyepi in Bali, Selamatan Laut in the northern coastal region of Java, and Syukuran Panen in agrarian communities, as culturally embedded pedagogical instruments for cultivating ecological ethos and strengthening environmental rights. Employing a qualitative conceptual approach, this research integrates socio-legal analysis, cultural studies, ecopedagogy, legal pluralism, and environmental justice theory to examine the intersection between indigenous ecological rituals, environmental education, and the right to a healthy environment. The study primarily relies on literature review, content analysis, and comparative conceptual mapping, supplemented by limited field observations conducted in coastal communities in Brebes, Northern Java, in 2024. The findings demonstrate that local ecological rituals embody conservation ethics, collective environmental responsibility, reciprocity between humans and nature, and socio-cultural mechanisms for transmitting ecological values across generations. Furthermore, the study argues that integrating ritual-based ecological knowledge into environmental education can strengthen environmental legal consciousness, support culturally responsive sustainability education, and contribute to the recognition of customary ecological practices within Indonesia’s pluralistic environmental governance framework. This study concludes that interdisciplinary collaboration among the fields of law, education, culture, and environmental governance is essential for developing inclusive and culturally rooted environmental policies capable of advancing ecological sustainability and environmental justice.